Origin of magnetic anomalies below the neel temperature in nanocrystalline LuMnO3 - Das, Raja; Jaiswal, Adhish; Adyanthaya, Suguna D.; Poddar, Pankaj (Journal of Physical Chemistry C, 2010)
Rare earth manganites crystallize in distorted orthorhombic perovskite or hexagonal structures and exhibit quite interesting optical and magnetic properties dictated by the size of the rare earth ion. Many of these materials might exhibit both ferroelectric and magnetic ordering as well as magnetoelectric coupling. However, their physical properties at reduced particle sizes remain underexplored due to the challenges associated with their synthesis with a proper control over the crystalline phase. Here, we report the wet-chemical synthesis of the hexagonal phase of nanocrystalline LuMnO3 with an average crystallite size of similar to 32 nm. The room-temperature Raman spectroscopy data are consistent with the calculated values of isomorphous hexagonal RMnO3 (R = rare earth atom) compounds with P6(3)cm symmetry. The UV-vis-NIR spectra recorded in the diffused reflectance mode at room temperature show electronic transitions at 1.7 eV (729 nm), 2.3 eV (539 nm), and 5 eV (258 nm). The magnetization measurements show that the Neel temperature for the LuMnO3 is situated at around 89 K, which is in close proximity to the reported value of the bulk phase. We also observed two unique and field-dependent magnetic anomalies that were predicted earlier but never reported experimentally. The first anomaly is observed as a sharp bifurcation in the ZFC-FC curves below 44 K at a 100 Oe applied field, which is accompanied with a sudden rise in the coercivity and magnetization. A second transition is observed at 12 K as a sharp peak in the ZFC curves, which is accompanied with a dip in coercivity. We attribute the transition at 44 K to the reorientation of the Mn3+ ions due to the Dzyaloshinskii-Moriya interaction, and the transition at 12 K is explained by weak antiferromagnetic coupling between Mn-O-Mn in the ab plane, which becomes dominant at lower temperatures.

Observation of enhanced dielectric coupling and room-temperature ferromagnetism in chemically synthesized BiFeO3@SiO2 core-shell particles - Shirolkar, Mandar M.; Das, Raja; Maity, Tuhin; Poddar, Pankaj; Kulkarni, Sulabha K. (Journal of Physical Chemistry C, 2012)
We report the effect of SiO2 coating on the structural, magnetic, and dielectric properties of chemically synthesized high-purity BiFeO3 particles. The assynthesized BiFeO3 particles demonstrate properties comparable with those reported for bulk BiFeO3. On the other hand, the structural measurement on BiFeO3@SiO2 shows that the SiO2 coating has anisotropically compressed the lattice of BiFeO3 particles and stimulates the variation in the electron density. This affects magnetic and dielectric behavior of material. Frequency-dependent dielectric constant study at low temperature (20-325 K) revealed slight reduction (8-10%) in the dielectric constant of BiFeO3@SiO2 particles compared to uncoated BiFeO3 particles. The study reveals five anomalies at 234, 206, 146, 84, and 25 K located in close proximity to the linear magnetodielectric coupling and spin reorientation transitions. The loss tangent (approximate to 10(-3)) and alternating current (ac) conductivity (approximate to 10(-8) Omega(-1)cm(-1)) of BiFeO3@SiO2 particles are orders of magnitude lower than those observed for the BiFeO3 particles. The magnetic measurement shows the existence of room-temperature ferromagnetism in BiFeO3@SiO2 particles with average value of magnetic moment per Fe atom approximate to 0.030 mu(B) and appreciable coercivity as high as 120 Oe. The canted spin structure in the surface shell of BiFeO3@SiO2 particles show an enhanced magnetic property and shifted hysteresis loop. The magnetic measurement in close proximity to dielectric transitions revealed enhanced magnetization, suggesting the presence of anisotropies. It has been observed that SiO2 coating alters the properties of BiFeO3 particles. Our dielectric and magnetic measurements show enhanced coupling among the electric and magnetic ordered parameters in BiFeO3@SiO2 core-shell particles compared to uncoated BiFeO3 particles. The magnetic and dielectric properties of SiO2-coated BiFeO3 are similar to nanoparticles of BiFeO3 where interface plays a significant role.

Observation of exchange bias below incommensurate antiferromagnetic (ICAFM) to canted A-type antiferromagnetic (cAAFM) transition in nanocrystalline orthorhombic EuMnO3 - Das, Raja; Poddar, Pankaj (RSC Advances, 2014)
Detailed ac and dc magnetic properties of orthorhombic EuMnO3 were studied using a nanocrystalline powder sample. Orthorhombic EuMnO3 nanoparticles of 45 nm average size were synthesised using a hydrothermal method. Zero field cooled (ZFC) and field cooled (FC) magnetisation shows anomalies at similar to 53, 44 and 24 K attributed to paramagnetic (PM) to an incommensurate antiferromagnetic phase (ICAFM), ICAFM to a canted A-type antiferromagnetic order (cAAFM) and spin reorientation transitions, respectively. No indication of a PM to ICAFM transition was observed in either the real or imaginary part of ac magnetisation. The real part of the ac magnetisation curve showed a peak at similar to 24.7 K and anomalies at similar to 46.8 and 21.8 K were observed in the imaginary part of ac magnetisation. Reduction in the width of the thermal hysteresis between the field cooling and heating magnetisation curve was observed with the nanocrystallites (similar to 1 K) compared with the bulk phase (similar to 3 K) EuMnO3. Isothermal magnetisation showed a large value of the exchange bias (2799 Oe at 3 K) below the ICAFM to cAAFM transition temperature.

Oxidant mediated one-step complete conversion of multi-walled carbon nanotubes to graphene quantum dots and their bioactivity against mammalian and bacterial cells - Biswas, Anupam; Khandelwal, Puneet; Das, Raja; Salunke, Gayatri; Alam, Aftab; Ghorai, Suvankar; Chattopadhyay, Samit; Poddar, Pankaj (Journal of Materials Chemistry B, 2017)
It is essential for any antibacterial agent (for clinical applications) that it should have high and selective toxicity towards bacterial cells only, and should not affect the human cells at the concentration used. Graphene quantum dots (GQDs) have emerged as a potential candidate for biomedical applications. However, a simple, low cost, safe, easy to execute, one-step synthesis of uniform and monodispersed GQDs with selective toxicity towards bacterial cells rather than mammalian cells is difficult to achieve. Herein, we have reported a one-step, low-cost, aqueous-phase, simple approach for the complete conversion of multi-walled carbon nanotubes into water-dispersible GQDs with an average size of similar to 3 nm using sodium bismuthate (NaBiO3) as a strong oxidant. The cyclic voltammetry and X-ray photoelectron spectroscopy results indicated that the as-synthesized GQDs suspension possess almost negligible amounts of metallic impurities. The cytotoxicity studies of GQDs against mammalian NIH 3T3 (mouse embryo fibroblast cells) and HEK 293T (human embryonic kidney cells) cells showed that the as-synthesized GQDs were non-cytotoxic up to the concentration of similar to 200 mu g mL(-1). The antimicrobial study shows that the synthesized GQDs have high and selective toxicity towards bacterial cells with a minimum inhibitory concentration of similar to 256 mu g mL(-1) for E. coli and B. subtilis and similar to 512 mu g mL(-1) for P. aeruginosa and S. aureus. The scanning electron microscopy and atomic force microscopy images show extensive cell damage via the perturbation of bacterial cell walls, which was consistent with the enhancement of reactive oxygen species production by almost two times in the bacterial cells upon incubation with similar to 256 mu g mL(-1) GQDs. Our study suggested that the as-synthesized GQDs can be used as a potential candidate for clinical applications as they possess high toxicity to bacterial cells and low toxicity to mammalian cells.